BAS/BSCR21 Akt protects the heart by promoting mitochondrial fusion. Issue 17 (26th August 2010) - Ong, S B; Arjun, S; Lim, S Y; Davidson, S M; Yellon, D M; Hausenloy, D J
Abstract : Background: Mitochondria change their morphology by undergoing 'fusion' and 'fission' to generate elongated and fragmented mitochondria, respectively. We hypothesised that inducing mitochondrial fusion protects the heart against ischaemia-reperfusion injury (IRI), and that this mechanism underlies the cardioprotection elicited by the pro-survival kinase, Akt. Methods/results: Inducing mitochondrial fusion in HL-1 cells (a cardiac cell line), using mitochondrial fusion proteins and a pharmacological inhibitor of a mitochondrial fission protein (called mdivi-1) delayed the opening of the mitochondrial permeability transition pore (mPTP, a critical mediator of IRI) and reduced cell death following IRI. Overexpressing Akt induced mitochondrial elongation (49.0±5.8% control vs 72.8±5.0% Akt; N=4 experiments:*p<0.05), delayed mPTP opening (twofold; N=4 experiments: p<0.05); and reduced cell death following IRI (64.9±5.6% control vs 34.2±1.2% Akt; N=4 experiments:*p<0.05). Treatment with the cytokine, erythropoietin (EPO, 10 U/ml), also induced mitochondrial elongation (30.0±3.5% with control vs 67.0±3.4% for EPO; N=4 experiments:*p<0.05), delayed mPTP opening (twofold; N=4 experiments: p<0.05); and reduced cell death following IRI (43.1±2.7% control vs 17.0±2.7% EPO; N=4 experiments:*p<0.05). Finally, elongated mitochondria extending 4–6 μm in length were observed in adult rodent hearts using electron and confocal microscopy. Treatment with mdivi-1 increased the number of elongated mitochondria and protected against IRI, as shown by reduced cell death in adult cardiomyocytes following IRI, and reduced myocardial infarct size in the in vivo murine heart. Conclusions: Inducing mitochondrial fusion protects the heart against IRI by delaying mPTP opening. Akt activation also promotes mitochondrial fusion, delays mPTP opening and protects against IRI. These results suggest that modulating mitochondrial morphology may be a novel strategy for cardioprotection.